Perfectionistic Concerns and Mobile Phone Addiction of Chinese College Students: The Moderated Mediation of Academic Procrastination and Causality Orientations - Liu, Guirong; Teng, Xiuqin; Fu, Yao; Lian, Qiang (Frontiers in Psychology, 2022)
The high occurrence rate, serious undesirable consequences and the risk factors of mobile phone addiction (MPA) have been well-established. Few studies, however, have examined the perfectionism – MPA link and the mechanism underlying it. Based on the perfectionism cognition theory (PCT), the temporal motivational theory (TMT), Psychological Decompensation Hypothesis, and self-determination theory (SDT), the present study aimed to investigate the effect of perfectionistic concerns (PC) on MPA and the mediating role of academic procrastination as well as moderating role of causality orientations (autonomous/controlled/impersonal orientation) in the link. A cross-sectional sample of 625 Chinese college students (20.8% male, mean age = 20.47 years old) completed measures of PC, academic procrastination, causality orientations, and MPA. Survey data were analyzed using SEM in Mplus 8.0. The results indicated that PC was positively related to MPA. And academic procrastination partially mediated this association. The hypothesized moderating effect of autonomous orientation and controlled orientation were not supported. Impersonal orientation moderated the relationship between academic procrastination and MPA. What’s more, impersonal orientation moderated the second stage of the mediating effect of academic procrastination on PC—MPA link. And the implications of the study for relieving or preventing college students’ MPA are also discussed deeply and thoroughly.